Navigating Public on the Rails: Politeness Strategies and Speech Acts in Indonesian Train Announcements - Susanti, Ratna; Arkida, Teisar; Tasyarasita, Aulia Zahra (REiLA : Journal of Research and Innovation in Language, 2025)
This study explores a crucial gap in the pragmatics of public communication by examining speech acts and politeness strategies in Indonesian train announcements. Using a qualitative descriptive approach rooted in pragmatics, data were collected through recordings and note-taking of both manual and automated announcements from long-distance (KAJJ) and commuter (KRL) trains. The analysis followed a four-stage framework: domain analysis identified operational contexts, taxonomic analysis categorized speech acts and politeness strategies, componential analysis examined patterns and variations, and cultural theme analysis connected linguistic features to broader cultural norms. Key findings revealed that KAJJ announcements prioritize directive speech acts framed by negative politeness and bald-on-record strategies to ensure clarity and passenger compliance. Conversely, KRL announcements blend assertive, expressive, and directive acts supported by positive politeness to foster inclusivity and encourage cooperation. Both services employ boosters to emphasize urgency, while the absence of hedges ensures directness. These findings underline how operational priorities shape linguistic choices, aligning communication strategies with passenger needs and cultural expectations. The study not only advances methodological rigor in analyzing public announcements but also provides practical recommendations for designing effective, culturally sensitive communication systems. These insights contribute to enhancing public transportation services and have broader implications for improving communication frameworks in high-stakes contexts worldwide.